Identifikasi Standar Kompetensi Kerja Nasional Indonesia (SKKNI) pada Pengembangan Kurikulum Program Studi Teknik Lingkungan - Fajrul Falakh (Journal on Education, 2022)
Identification of competency standards is an important step for study programs to ensure that the vision, mission, goals and profiles of graduates in the study program are in line with the needs of graduate users (business and industry). As an effort to realize the competency quality of prospective graduates so that they are in accordance with the competency needs in the industrial world, the Environmental Engineering Study Program has identified the relevance of the curriculum to the Indonesian National Work Competency Standards (SKKNI). This study is the result of identifying competency needs based on SKKNI in the Environmental Engineering Study Program, Walisongo State Islamic University, Semarang. The identification method uses focus group discussions (FGD) and literature studies. It is hoped that this article can become the basis for academic studies on curriculum development in the Environmental Engineering Study Program so that it is suitable for meeting competency needs in the world of work. The results of this study can also be developed for the preparation of a Training Need Analysis (TNA) for career preparation for prospective graduates. The SKKNI search in this study was classified into three main fields according to the graduate profiles of the study programs, namely: the field of Engineering, the field of Environment and the field of Occupational Health Safety (K3). as material for studying the formation of an SKKNI-based curriculum in the Environmental Engineering Study Program, Walisongo State Islamic University, Semarang.